2017
DOI: 10.3892/ol.2017.6467
|View full text |Cite
|
Sign up to set email alerts
|

TRIM59 is a novel potential prognostic biomarker in patients with non-small cell lung cancer: A research based on bioinformatics analysis

Abstract: Lung cancer is the leading cause of cancer-associated mortality worldwide and its prognosis is poor. Few effective biomarkers for non-small cell lung cancer (NSCLC) have been translated into the clinical practice aiming to assist in the treatment plan design and prognosis evaluation. The aim of the present study was to identify novel potential prognostic biomarkers for NSCLC. Tripartite motif 59 (TRIM59) was identified from a microarray dataset of matched-samples and was verified as an aberrantly upregulated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…TriM67, located at chromosome 11q22-23, encodes a 783 amino acid protein with listBox zinc-finger motifs and an adjacent leucine-zipper motif. TRIM67 was identified to be significantly downregulated in NSCLC cell lines (11), which was additionally confirmed by Hao et al (20), who suggested that TriM67 may be a tumor suppressor gene. The functions of TriM67 are largely unclear.…”
Section: Discussionsupporting
confidence: 56%
“…TriM67, located at chromosome 11q22-23, encodes a 783 amino acid protein with listBox zinc-finger motifs and an adjacent leucine-zipper motif. TRIM67 was identified to be significantly downregulated in NSCLC cell lines (11), which was additionally confirmed by Hao et al (20), who suggested that TriM67 may be a tumor suppressor gene. The functions of TriM67 are largely unclear.…”
Section: Discussionsupporting
confidence: 56%
“…TRIM59, a member of the TRIM family of proteins, serves a crucial role in the proliferation and metabolism of several types of cancer, such as lung (17,18) and gastric cancer (19). TRIM59 protein functions as an E3 ubiquitin ligase, and is comprised of an N-terminal really interesting RING-finger domain (1).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, hypermethylation of TRIM58 in lung cancer may account for its down-regulation (Diaz-Lagares et al, 2016). Overexpression of TRIMs 11,22,44,47,59, and 65 were correlated with poor prognosis in lung cancers (Liu et al, 2013;Wang X.-L. et al, 2016;Xing et al, 2016;Han et al, 2017;Hao et al, 2017;Liu et al, 2017b;Huang et al, 2019;Yin et al, 2019). Overexpression of TRIM44 induced mTOR signaling, epithelial-mesenchymal transition, and cyclin/CDK upregulation in lung cancer cells (Xing et al, 2016).…”
Section: Lung Cancermentioning
confidence: 99%